Effects of MGA and PGF on estrus induction and synchronization in cows and heifers - Boyd, G.W.; Patterson, D.J.; Corah, L.R.; Brethour, J.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three trials were conducted in the spring of 1985 to evaluate the effectiveness of MGA feeding and Prostaglandin (PGF) injection on estrus induction and synchronization. Trials 1 and 2 were both done on a Kansas ranch and involved 70 heifers and 86 cows, respectively. In both trials, all cycling and non-cycling females were fed MGA (7 days in trial 1, 9 days in trial 2) and half of the cows and heifers received a PGF injection. The estrus response was higher (P<.0l) for the cycling heifers with the combination treatment. Both treatments resulted in similar first service conception rates and both were effective in inducing estrus in noncycling heifers. Only a small percentage of the cows in trial 2 were cycling prior to the treatments and only a small percentage of the non-cycling cows responded to the MGA. In trial 3, half of the cycling heifers were fed MGA for 7 days and PGF was injected on day 7. Response to synchronization peaked 96 to 120 hr following MGA withdrawal. Among F1 Angus X Hereford heifers, the MGA-PGF treatment reduced (P<.0l) first service conception rates as compared to controls (55 vs 80%), although a reduction was not seen with F Brahman X Hereford heifers. Conversely, 45-day pregnancy rates tended to be higher among both groups of synchronized heifers (P>.05). The MGA treatment also initiated cyclicity in prepuberal females of both crosses.
Keywords: Beef; MGA; PGF; Estrus; Synchronization